Methodological recommendations on the application of Iverlong long acting preparation in the presence of parasitic diseases of livestock animals - E. S. Engasheva (Российский паразитологический журнал, 2019)
Methodological recommendations on the application of Iverlong long acting preparation in the presence of parasitic diseases of livestock animals are given, including general data, pharmacological properties, application procedure and personal preventive measures. Iverlong is prescribed to cattle and sheep for the treatment and prophylaxis of nematodosis (dictyocaulosis, strongylatosis, strongyloidosis, neoascaridosis, bunostomosis, thelaziosis), gasterophilidae invasions (hypodermatosis, oestrosis), psoroptic scab, sarcoptic scab, sifunculatosis. Iverlong is administered to the animals as a single dose intramuscularly or subcutaneously to cattle on brachium, it is administered to sheep in the internal surface of thigh in a dose of 1 ml per 50 kg of body weight. Iverlong provides protection of animal from parasitic diseases up to 75-90 days.